Translating Tea: On the Semiotics of Interlingual Practice in the Hong Kong Museum of Tea Ware - Neather, Robert (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis paper explores the nature of interlingual translation practice in the museum, focusing in particular on the ways in which visual elements shape or constrain the translation of verbal texts. The museum represents a particularly complex semiotic environment in which various systems of signification (verbal, visual, spatial) interact to produce meaning in a way that is said to be “combinatorial and relational.” Such interactions take place both at intra-semiotic levels (e.g. between objects, between objects and photographs, or between texts) and inter-semiotic levels (between these various verbal and visual elements). Interlingual translation must negotiate such multiple polarities if an effective target text is to be produced. The paper focuses on the Museum of Tea Ware in Hong Kong, to examine how various semiotic constraints affect the production of English target texts from their Chinese source texts. One such constraint is that of spatial aesthetics, the way in which text is positioned in relation to visually salient pictures or objects in a given ensemble. A second constraint is the generic nature of the text as defined by its position in the museum text-hierarchy. Thirdly, the paper argues at greater length that the nature of modification found in the target text is directly proportional to whether the relation between given verbal and visual elements is either paradigmatic or syntagmatic.